State Ownership Heterogeneity and Corporate Innovation: New Evidence from a Hierarchical Perspective - Pu, Tingqian; ZulkafliAbdul Hadi (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2024)
Unlike prior research, this study re-examines the relationship between state ownership and corporate innovation from a hierarchical perspective. Drawing upon institutional theory, our findings reveal the heterogeneous impact of state ownership, elucidating the positive role of central state ownership in fostering corporate innovation, while highlighting the inhibitory effect of local state ownership. This conclusion withstands rigorous scrutiny through a battery of robustness checks. Mechanism analysis indicates that central state-owned enterprises stimulate innovation by increasing innovation investment and enhancing efficiency, whereas local state-owned enterprises create obstacles for both innovation investment and efficiency. Our paper offers a hierarchical interpretation of the mixed evidence regarding the relationship between state ownership and corporate innovation. Whether state ownership serves as a facilitator or a hindrance to innovation depends on whether central or local state-owned enterprises dominate the national innovation process. Overall, this study offers new insights into the complex effects of state ownership heterogeneity on corporate innovation activities in emerging economies like China, advancing our understanding of the subtle relationship between corporate governance and innovation.